Transcriptomic analysis links diverse hypothalamic cell types to fibroblast growth factor 1-induced sustained diabetes remission - Marie A. Bentsen (Nature Portfolio, 2020)
In rodent models of type 2 diabetes, sustained remission of hyperglycemia can be induced by FGF1 action in the mediobasal hypothalamus. Here, the authors show that FGF1-injection is followed by marked changes in glial cell populations and that the sustained glycemic response is dependent on intact melanocortin signaling.